Exploring the Impact of Diabetes Mellitus on Clinical Outcomes in Patients Following Severe Traumatic Brain Injury Using the TriNetX Database - Kamal Shaik; Spencer Rasmussen; Rudy Rahme; Michael Karsy (Surgeries)
Introduction: Traumatic brain injury (TBI) involves a diverse group of head blunt and/or penetrating injuries and is a leading cause of death in the U.S., accounting for one-third of all injury-related deaths. A post-injury hyperglycemic state may commonly impact TBI prognosis and strongly correlate with injury severity. Diabetes mellitus (DM) may also be a source of concomitant hyperglycemia that can worsen prognosis, with previous literature suggesting that DM could be an independent predictor of poor outcome and mortality after TBI. Methods: Using the multi-center, national TriNetX database, we performed a propensity score-matched analysis of severe TBI patients with (DM) and without DM (NDM) from 2014 to 2024. We examined the risk of mortality and complications, including sepsis, cerebral infarction, and pulmonary embolism. We also performed a sub-group analysis comparing the risk of mortality and complications between patients with either insulin-dependent or insulin-independent forms of DM. Results: A total of 26,019 patients were included (4604 DM vs. 21,415 NDM). After propensity score matching, patients with DM had a significantly lower risk of mortality (RR: 0.815; 95% CI: 0.771–0.861; p < 0.05) and ventilator dependency (RR: 0.902; 95% CI: 0.844–0.963; p < 0.05) compared to NDM patients. However, patients with DM had a significantly higher risk of cerebral infarctions, seizures, pneumonia, and sepsis (p < 0.05). Sub-group analysis found no significant difference in mortality or complications between insulin-dependent and insulin-independent forms of DM. Conclusion: Our results suggest that hyperglycemia secondary to DM plays a complicated role in the outcomes after severe TBI. Unexpectedly, we identified both increased and decreased complications in patients with DM. These results reflect the current challenges in the literature surrounding pre-existing DM in patients’ outcomes, the impact of diabetic medications on patient outcomes, and the changing role of aggressive glucose management in critical care patients.